Online news coverage on relaxation of alcohol sales during lockdown following COVID-19 in India: missing the forest for the trees?. (3rd September 2021) - Singh, Swarndeep; Chandiok, Ketaki; Singh Balhara, Yatan Pal
ABSTRACT: Background : Several relaxations were announced by the Indian government during the third phase of lockdown (3.0), including permission to resume alcohol sales. This generated great interest and was covered extensively by news media. The present study aimed to examine online news coverage on this relaxation of alcohol sales. Methods : Relevant information related to news report characteristics was extracted under predecided headings and analyzed. Results : The most common themes were: status of alcohol sales across the different state(s), government officials', and politicians' response, potential harms of allowing alcohol sales during the lockdown, and pitching for online sale or home-deliveryof alcohol during the lockdown. The news reports advocating online sale and home delivery of alcohol (p = .001), and demanding, or suggesting reforms in alcohol sales policy (p = .02) were found to be independently associated with an overall favourable stance on allowing alcohol sales during the lockdown. Only aminority (12.1%) discussed its public health implications, and need for scaling up preventive and treatment services for alcohol use disorder (3%). Conclusion : The narrative presented in the online media failed to offer acomprehensive reporting on various relevant aspects related to the resumption of alcohol sales during lockdown 3.0 in India.